ФОРМУВАННЯ УЗБЕЦЬКОЇ ЕТНІЧНОЇ ГРУПИ НА ПІВДНІ УКРАЇНИ (ХХ – ПОЧ. ХХІ СТОЛІТТЯ) (Zaporizhzhia Historical Review, 2021)
The historical preconditions, the main stages and peculiarities of the present foundation of uzbek ethnic group in South Ukraine have been investigated in the article. Separate aspects of the development nationalcultural life development of uzbek national minority in Ukraine have been analysed.